KOMUNIKASI ORANG TUA DAN PERILAKU SEKSUAL REMAJA SEKOLAH MENENGAH KEJURUAN DI KOTA BATURAJA - Sari, Desi Kurnia; Taviv, Yulian (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Background: High risk teenage sexual behavior has become a problem of the community. Negative impact of such behavior is fatal for the future of teenagers and quality of future generation. Parents' communication has a major role in teenage sexual behavior. Objective: To analyze role of parents' communication in the prevention of high risk teenage sexual behavior. Method: The study was observational with cross sectional design. Data were obtained through indepth interview. Sampling used multi stage random sampling with as many as 250 respondents of grade III vocational school at Baturaja Municipality determined with proportional technique. Data analysis used univariate, bivariate, and multivariate methods. Result: Parents' communication was associated with teenage sexual behavior. The prevalence of high risk teenage sexual behavior was 1.7 times higher (RP=1.7 CI 95%=1.13-3.83) in parents having poor communication. Parents' communication could predict the incidence of high risk teenage sexual behavior as much as 9.3% after being controlled with variable of age, religiousity, media and peer. The result of analysis through indepth interview with teenagers sexually active showed there was communication about sexuality between parents and teenagers that was less open, content of moral massage was not clear and method of delivery was inconvenient. Conclusion: Communication about sexuality given by parents and at early age had important role in preventing high risk teenage sexual behavior. Message of sexuality should be given moreoften and with good quality. Content of sexuality message should be emphasized on moral values, method on how to control sexual drive healthily and according to religious belief, more selective in choosing friends and avoiding exposure from media of pornography.